PERANCANGAN SISTEM PENGUKURAN KINERJA MENGGUNAKAN METODA PERFORMANCE PRISM - Naniek Utami Handayani; Haryo Santoso; Siti Rochmawati (Teknoin, 2005)
XYZ company is a printing and publishing company, especially for lesson and education books with more than 50 branch offices in Indonesia. As a profit oriented organization, so far performance measures of this company only based on financial aspect. Whereas, non financial aspect and stakeholder wants and needs ignored and didn’t get enough attention. So, it is difficult to know overall company performance exactly. Therefore, required new performance measurement system that can describe company performance more comprehensive and integrated. This research use performance prism method to design the new performance measurement system because it is more suitable and representative with the objective condition of XYZ company than other models.The result of design describe that stakeholders of XYZ company are including: customers, employees, investors and owners, suppliers, regulators and local communities. Measurement system obtained 31 Key Performance Indicators(KPI) including 3 KPI of customers, 9 KPI of general employees, 4 KPI of production employees, 7 KPI of investor and owners, 3 KPI of suppliers, and 5 KPI of regulators and local communities. Result of implementation performance measurement system with scoring system using OMAX method indicates that amount of scor current performance indicator is 69%. From overall KPI, these are 4 KPI with bad performance criteria, that is amount of customer’s complaint, amount of eployee’s complaint with completion, increase of production volume and amount of late delivery of employee’s monthly report. Result of measurement can be based for doing evaluation and choice planning improvement organization,  so all stakeholder requirements can be fulfilled.Keywords : Performance Prism, performance measurement, stakeholder